DEMOCRACIA Y CONFLICTO EN VENEZUELA (1988-2008) - Romero, Juan Eduardo (2009)
This paper addresses the issue of democracy in Venezuela from a manifold and varied. Part of the consideration of a set of variables (role of the state in the globalized society, politics and governance, economics, social policy, social movements and collective protests, environment and ethnic groups) to make a weighting of the course and the challenges of Venezuelan democratic society in the period 1988-2008. The work runs the analysis from the perspective of historical comparison, the critical history, sociology, history and political thought to establish the main trends that have purchased Venezuelan democracy in each of these variables in the period studied, as well as foresight they can acquire in the coming years.